Pengaruh Social Presence dan Scarcity terhadap Impulse Buying melalui Emotion pada Konsumen Shopee Live - Erza Rifky Afriansyah; Muhammad Dzaky; Sri Vandayuli Riorini (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Live streaming commerce has transformed online shopping behavior as interactive features and real-time promotions increase emotional engagement and trigger impulsive actions. Shopee Live is one of the platforms where social interaction and urgency cues strongly influence consumer decisions. This study examines how social presence from broadcasters, viewers, and the live streaming environment, along with scarcity cues, shapes impulse buying through emotional responses. A quantitative explanatory design was used. Data were gathered from 137 Shopee Live users through an online questionnaire. The analysis employed Partial Least Squares Structural Equation Modeling to assess direct and indirect relationships within the Stimulus Organism Response framework. Social presence from broadcasters, viewers, and the overall live setting significantly enhances pleasure, which subsequently drives impulse buying. Scarcity also increases pleasure by creating urgency that stimulates spontaneous decisions. Emotional reactions serve as a mediating factor linking social presence and scarcity to impulse buying in live streaming commerce. The findings broaden the understanding of digital consumer behavior and offer insights for online sellers and e-commerce platforms aiming to optimize live streaming strategies.